Archaeology [videorecording] - Foiles, Stacey; Grant, Eleanor; Naughton, Tom.; Valcour, Nicholas; The Archaeological Institute of America ([S.l.] Discovery Communications, 1994)
Discovers the raw archaeological materials that gives insights as to who were the Philistines and the historical counterpart to the scriptural people who harassed the Israelites for many generations. Scientists find proofs of the killer quakes in the bible in the ruins of ancient sites.
Last days of Philistines (29 min.) -- Killer quakes of the bible (26 min.)
Title from cover: Archaeology : last days of Philistines, killer quakes of the bible.
VHS.
Credits : Host, John Rhyss-Davies.
Story consultants, Archaeology Magazine Phyllis Palak Katz & Peter A. Young; Editor, David McCurley.
Keywords: Archeology -- Palestine; Philistines -- History; Palestine -- Antiquities